2001
DOI: 10.2118/69211-pa
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced 2D Proppant-Transport Simulation: The Key To Understanding Proppant Flowback and Post-Frac Productivity

Abstract: Summary It has been assumed that along with fluid viscosity and pump rate, gravity dominates final proppant placement in hydraulic fractures. Results here, based on detailed multiphase-flow modeling, show that other factors such as slurry rheology (effect of adding proppant on slurry viscosity), fluid loss and layered fluid loss, and vertical fracture-width variations often are more important than gravity in controlling placement. Abstract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Their numerical results suggest a high leakoff restricts the spread of proppant along the direction of fracture propagation. Moreover, Smith et al [306] concluded that leakoff and the heterogeneity of formation can dramatically change the proppant distribution when the fracture shuts in. Another phenomenon resulting from leakoff is screen-out [334].…”
Section: Leakoffmentioning
confidence: 99%
See 1 more Smart Citation
“…Their numerical results suggest a high leakoff restricts the spread of proppant along the direction of fracture propagation. Moreover, Smith et al [306] concluded that leakoff and the heterogeneity of formation can dramatically change the proppant distribution when the fracture shuts in. Another phenomenon resulting from leakoff is screen-out [334].…”
Section: Leakoffmentioning
confidence: 99%
“…Another example of the P3D model is MFrac (Meyer Fracturing simulators), which has been developed since 1986 [204,205] and is widely used by the petroleum engineering industry. Some other examples and applications of the P3D model can be found in [9,127,306]. Comparisons between 2D models (the PKN model and the KGD model) and the P3D model were conducted by Rahim and Holditch [251] and Rahman and Rahman [255].…”
Section: Pseudo 3d (P3d) Modelmentioning
confidence: 99%
“…Qi et al 23 developed a prediction model for proppant flowback, and this model coupled both the fracture shunt model and critical rate model. Smith et al 24 conducted numerical simulation, which considered fluid rheology, fluid loss, gravity, proppant concentration, viscosity, changes in fracture geometry, and in-site stress to model proppant flowback. Hu et al 25 proposed a mechanical model for proppant flowback before and after the fracture closure.…”
Section: Introductionmentioning
confidence: 99%
“…Mixing proppant with a Newtonian fluid has been investigated in [1,28,50,68], and with polymers in [64], [24], [69], [48] to name a few. These numerical studies have been performed using boundary element methods, discrete fracture networks or extended/generalized finite elements and have mainly treated 2D planar fractures.…”
Section: Introductionmentioning
confidence: 99%